Compact Dual-Band Coupler for Vehicular Beam-Forming Array - Dakui Wu; Guoxin Zheng (International Journal of Antennas and Propagation)
A novel kind of compact dual-band quadrature patch coupler for vehicular beam-forming array is proposed for the first time in this paper. To keep the performance of the first operating frequency 2.4 GHz (for Bluetooth Low Energy (BLE)) and generate the second operating frequency 5.9 GHz (for Dedicated Short Range Communications (DSRC)) simultaneously, complementary triangular split resonant rings (CTSRRs) and splitting gaps are employed to improve the performance of this new coupler; final size of the proposed coupler is 0.24λg (for 2.4 GHz). To validate the performance and design method of the coupler this paper proposed, a 3D model is constructed and optimized with ANSOFT HFSS firstly and then a coupler prototype is fabricated and measured. The measured results show that the amplitude unbalance (AU) is 0.54 dB and 0.44 dB for 2.4 GHz and 5.9 GHz, respectively, and the corresponding phase unbalance (PU) is 93.5 and 92 degrees, respectively.